Cobalt-free sodium ion battery positive electrode material as well as preparation method and application thereof
By introducing ions of different valence states to replace nickel ions in the sodium ion battery positive electrode material, the cobalt-free P2 layered oxide positive electrode material is prepared, which solves the phase transition problem of the sodium ion battery positive electrode material when the charging voltage increases, and significantly improves the The cycle stability and capacity of the material are obtained.
Patent Information
- Application Number
- CN202411535135.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-07
AI Technical Summary
The existing sodium ion battery positive electrode materials will undergo irreversible phase transitions when the charging voltage increases, resulting in huge changes in the unit cell volume, seriously affecting the cycle life of the battery.
By introducing ions of different valence states into nickel sites in transition metals, a cobalt-free P2-type layered oxide positive electrode material is prepared. The chemical formula is Na0.67NixM1yM2zMn0.67O2, and M1 and M2 are Mg and Cu , any two types of Li, Zn or Fe, x+y+z=0.33, magnesium ions, copper ions, lithium ions, zinc ions, and iron ions replace part of nickel ions.
Improve the cyclic stability of the material and maintain considerable capacity. The capacity is around 100-110mAh/g at a current density of 1C, and a capacity of 80-90mAh/g can still be obtained under a high current density of 5C, and cycling is 400. Circle or above.
Smart Images

Figure CN119400851A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion positive electrode materials, and in particular relates to a cobalt-free sodium ion battery positive electrode material and a preparation method and application thereof. Background Art
[0002] Fossil fuels are non-renewable and cannot be restored once consumed. In addition, they may cause environmental pollution during use, affecting the sustainable development of the ecological environment and making it difficult to meet the energy needs of "green and low-carbon". Therefore, it is of great strategic significance to develop a new generation of renewable energy technologies. Energy storage technology can better solve the problem of balanced development of energy and environment and has received widespread attention. In recent years, due to the scarcity of lithium resources and the increasing mining costs, its large-scale application in energy storage systems has been greatly restricted. Sodium and lithium are in the same main group and have similar chemical properties. Sodium is abundant in the earth's crust and is inexpensive. It is gradually becoming a substitute for lithium in the field of energy storage. More importantly, sodium-ion batteries have considerable high and low temperature performance and good safety, making them very suitable for large-scale applications.
[0003] As we all know, sodium-ion batteries are composed of components such as positive electrodes, negative electrodes, electrolytes and diaphragms, and each component performs its own function. Among them, the positive electrode material plays a decisive role in the performance of sodium-ion batteries, affecting important parameters such as energy density, power density, and cycle life. Therefore, the development of positive electrode materials with high specific capacity, high energy density, and high operating voltage has become the primary problem to be solved. In order to obtain high-performance positive electrode materials, layered oxide type, polyanion type, Prussian blue type, etc. have been developed. Compared with the latter two, the layered oxide type has the advantages of simple synthesis, high specific capacity, and high operating voltage, and is more suitable for large-scale production. The P2-type layered oxide has better air stability than the O3 type, but with the increase of charging voltage, while increasing the specific capacity, it also causes an irreversible phase transition process, resulting in a huge change in the unit cell volume, which seriously affects the cycle life of the battery. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a cobalt-free sodium ion battery positive electrode material, which improves the cycle stability of the material and maintains a considerable capacity of about 100-110 mAh / g at a current density of 1C by introducing ions of different valence states into the nickel site of the transition metal. Even at a high current density of 5C, a capacity of 80-90 mAh / g can be obtained and cycled for more than 400 cycles.
[0005] The technical solution of the present invention is as follows:
[0006] The present invention discloses a cobalt-free sodium ion battery positive electrode material, wherein the positive electrode material is a P2-type layered oxide material, and its general chemical formula is Na0.67 Ni x M1 y M2 z Mn 0.67 O2, wherein M1 and M2 are any two of Mg, Cu, Li, Zn or Fe, x>0, y>0, z>0, and x+y+z=0.33, and magnesium ions, copper ions, lithium ions, zinc ions and iron ions replace part of the nickel ions.
[0007] The present invention also discloses a method for preparing the above-mentioned positive electrode material, comprising the following steps:
[0008] (1) according to the stoichiometric ratio of the chemical formula, a sodium salt in an amount of 1 to 1.05 times the stoichiometric amount of the required sodium element is mixed with the remaining metal salts in the required amount;
[0009] (2) After drying, sintering at 500-900° C. for 4-20 h, and cooling to room temperature to obtain the positive electrode material.
[0010] In one embodiment of the present invention, the sodium salt in step (1) is carbonate, acetate or oxalate, and the remaining metal salts are one or more of carbonate, acetate or oxalate.
[0011] In one embodiment of the present invention, before preparing the positive electrode material, the feasibility thereof is verified: 0.67 Ni 0.33 Mn 0.67 Take sodium salt, nickel salt and manganese salt and mix them evenly. Collect the powder after mixing and dry it. Transfer it to a muffle furnace and sinter it at 500-900℃ for 4-20h to obtain Na 0.67 Ni 0.33 Mn 0.67 O2 material.
[0012] In one embodiment of the present invention, the method further comprises grinding the cooled positive electrode material into powder in a mortar, transferring the powder into a centrifuge tube, sealing the tube, and storing the tube in an argon glove box for later use.
[0013] The present invention also discloses a sodium ion battery positive electrode plate, wherein the positive electrode plate comprises the positive electrode material.
[0014] The invention also discloses a sodium ion secondary battery comprising the positive electrode plate.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] A cobalt-free sodium ion battery positive electrode material of the present invention is obtained by a specific element substitution strategy to obtain a positive electrode material suitable for sodium ion batteries, and the positive electrode material exhibits excellent performance. By introducing ions of different valence states into the nickel site of the transition metal, the cycle stability of the material is improved and a considerable capacity is maintained. The capacity is about 100-110 mAh / g at a current density of 1C. Even at a high current density of 5C, a capacity of 80-90 mAh / g can still be obtained, and more than 400 cycles can be cycled. Due to the use of cheap metal salts, certain advantages are reflected in terms of cost; during the synthesis process, no side reactions are generated, reflecting the characteristics of environmental friendliness; compared with the traditional sol-gel method and hydrothermal synthesis method, the present invention does not need to prepare a precursor, and a cobalt-free layered oxide positive electrode material can be obtained by simply mixing various metal salts, which has the characteristics of simple operation. In the process of synthesizing the positive electrode material by high-temperature sintering, the temperature range used is in the range of 500-900°C, and does not involve 1000°C synthesis, which is conducive to reducing energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 A cobalt-free sodium ion battery positive electrode material Na 0.67 Ni 0.33 Mn 0.67 The charge and discharge curve of O2 at 0.2C current density;
[0018] Figure 2 The cobalt-free sodium ion battery positive electrode material Na in Example 2 of the present invention 0.67 Ni x Li y Mg z Mn 0.67 Cycling performance diagram of O2 (x=0.2, y=0.08, z=0.05) at 5C current density;
[0019] Figure 3 A cobalt-free sodium ion battery positive electrode material Na is provided in Example 6 of the present invention. 0.67 Ni x Li y Mg z Mn 0.67 SEM image of O2 (x=0.19, y=0.08, z=0.06);
[0020] Figure 4 A cobalt-free sodium ion battery positive electrode material Na is provided in Example 6 of the present invention. 0.67 Ni x Li y Mg z Mn 0.67XRD pattern of O2 (x=0.19, y=0.08, z=0.06);
[0021] Figure 5 A cobalt-free sodium ion battery positive electrode material Na is provided in Example 6 of the present invention. 0.67 Ni x Li y Mg z Mn 0.67 Rate performance diagram of O2 (x=0.19, y=0.08, z=0.06);
[0022] Figure 6 A cobalt-free sodium ion battery positive electrode material Na is provided in Example 6 of the present invention. 0.67 Ni x Li y Mg z Mn 0.67 Cycling performance diagram of O2 (x=0.19, y=0.08, z=0.06) at 1C current density;
[0023] Figure 7 A cobalt-free sodium ion battery positive electrode material Na is provided in Example 6 of the present invention. 0.67 Ni x Li y Mg z Mn 0.67 Cycling performance diagram of O2 (x=0.19, y=0.08, z=0.06) at 5C current density. DETAILED DESCRIPTION
[0024] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0025] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.
[0026] A cobalt-free sodium ion battery positive electrode material according to an embodiment of the present invention, wherein the positive electrode material is a P2-type layered oxide material, and its general chemical formula is Na 0.67 Ni x M1 y M2 z Mn 0.67O2, wherein M1 and M2 are any two of Mg, Cu, Li, Zn or Fe, x>0, y>0, z>0, and x+y+z=0.33, magnesium ions, copper ions, lithium ions, zinc ions, and iron ions replace part of the nickel ions, and the preparation method thereof comprises the following steps:
[0027] (1) according to the stoichiometric ratio of the above chemical formula, a sodium salt in an amount of 1-1.05 times the stoichiometric amount of the required sodium element is mixed with the remaining metal salts in the required amount; the sodium salt is carbonate, acetate or oxalate, and the remaining metal salts are one or more of carbonate, acetate or oxalate;
[0028] (2) After drying, the metal salt is placed in a muffle furnace, sintered at 500-900° C. for 4-20 hours, and then cooled to room temperature to obtain the positive electrode material.
[0029] (3) The cooled positive electrode material is placed in a mortar and ground into powder, then transferred to a centrifuge tube, sealed, and stored in an argon glove box for later use.
[0030] Before preparing the positive electrode material, the feasibility of the positive electrode material is verified to see whether it can be used as a positive electrode material for a sodium ion battery. The positive electrode material must at least have a high specific capacity, including: 0.67 Ni 0.33 Mn 0.67 Take sodium salt, nickel salt and manganese salt and mix them evenly. Collect the powder after mixing and dry it. Transfer it to a muffle furnace and sinter it at 500-900℃ for 4-20h to obtain Na 0.67 Ni 0.33 Mn 0.67 O2 material.
[0031] Preparation of battery: Na 0.67 Ni 0.33 Mn 0.67 The O2 electrode material is mixed with the Super-P conductive agent and the polyvinylidene fluoride binder in a mortar at a mass ratio of 8:1:1. NMP is added to prepare a slurry and evenly coated on an aluminum foil. After drying in an ordinary oven, it is transferred to a vacuum drying oven; then it is cut into a circular electrode sheet with a diameter of about 12 mm as the positive electrode, and the sodium sheet is used as the negative electrode to assemble a button battery. Performance test: The constant current charge and discharge cycle test of the prepared samples is performed in a Xinwei battery tester with a voltage window of 2.5-4.3V. Before the test, the parameters required for the test are input including active materials, current density and other conditions. Its first charge and discharge curve is as follows Figure 1 As shown, at a current density of 0.2C, the first charge specific capacity is 160.9mAh / g, and the first discharge specific capacity is 144.1mAh / g. 0.67 Ni 0.33 Mn0.67 Although O2 exhibits high capacity, its capacity decays rapidly after cycling due to the instability of the transition metal layer and the sodium layer during the charge and discharge process.
[0032] Example 1
[0033] A cobalt-free sodium ion battery positive electrode material according to embodiment 1 of the present invention is prepared by the following steps:
[0034] (1) Mg / Cu co-substituted Na 0.67 Ni x Mg y Cu z Mn 0.67 O2 positive electrode material, wherein x=0.11, y=0.11, z=0.11; with a total mass of about 2 g, sodium carbonate, nickel acetate, magnesium acetate, copper acetate, and manganese carbonate are mixed according to the stoichiometric amount shown, and after mixing evenly, the powder is placed in a drying oven at 80°C for drying;
[0035] (2) The uniformly mixed powder is placed in an alumina crucible and transferred to a muffle furnace for high-temperature sintering. The sintering procedure is to heat at 600°C for 8 hours and naturally cool to room temperature to obtain a positive electrode material.
[0036] (3) Collect the bulk material in the alumina crucible, grind it into powder, and store it in an argon glove box for future use.
[0037] The battery assembly process is the same as above, and can exhibit an initial discharge specific capacity of 110 mAh / g at a current density of 1 C, and an efficiency of 85% after 50 cycles.
[0038] Example 2
[0039] A cobalt-free sodium ion battery positive electrode material according to embodiment 2 of the present invention is prepared by the following steps:
[0040] (1) Lithium / Mg co-substituted Na 0.67 Ni x Li y Mg z Mn 0.67 O2 positive electrode material, wherein x=0.2, y=0.08, z=0.05; with a total mass of about 2 g, sodium carbonate, nickel acetate, lithium acetate, magnesium acetate, and manganese carbonate are mixed according to the stoichiometric amount shown, and after mixing evenly, the powder is placed in a drying oven at 80°C for drying;
[0041] (2) The uniformly mixed powder is placed in an alumina crucible and transferred to a muffle furnace for high-temperature sintering. The sintering procedure is to heat at 900°C for 12 hours and cool naturally to room temperature to obtain a positive electrode material.
[0042] (3) Collect the bulk material in the alumina crucible, grind it into powder, and store it in an argon glove box for future use.
[0043] The battery assembly process is the same as above, such as Figure 2 As shown, it exhibits an initial discharge specific capacity of 92.5 mAh / g at a current density of 5 C, and an efficiency of 76.2% is obtained after 400 cycles.
[0044] Example 3
[0045] A cobalt-free sodium ion battery positive electrode material according to embodiment 3 of the present invention is prepared by the following steps:
[0046] (1) Zn / Fe co-substituted Na 0.67 Ni x Zn y Fe z Mn 0.67 O2 positive electrode material, wherein x=0.17, y=0.08, z=0.08; with a total mass of about 2 g, sodium carbonate, nickel acetate, zinc acetate, iron oxalate, and manganese carbonate are mixed according to the stoichiometric amount shown, and after mixing evenly, the powder is placed in a drying oven at 80°C for drying;
[0047] (2) The uniformly mixed powder is placed in an alumina crucible and transferred to a muffle furnace for high-temperature sintering. The sintering procedure is to heat at 800°C for 12 hours and cool naturally to room temperature to obtain a positive electrode material.
[0048] (3) Collect the bulk material in the alumina crucible, grind it into powder, and store it in an argon glove box for future use.
[0049] The battery assembly process is the same as above. At a current density of 1C, it can exhibit an initial discharge specific capacity of 95 mAh / g, and an efficiency of 82% after 100 cycles.
[0050] Example 4
[0051] A cobalt-free sodium ion battery positive electrode material according to embodiment 4 of the present invention is prepared by the following steps:
[0052] (1) Copper / iron co-substituted Na 0.67 Ni x Cu y Fe z Mn 0.67 O2 positive electrode material, wherein x=0.21, y=0.06, z=0.06; with a total mass of about 2 g, sodium carbonate, nickel acetate, copper acetate, iron oxalate, and manganese carbonate are mixed according to the stoichiometric amount shown, and after mixing evenly, the powder is placed in a drying oven at 80°C for drying;
[0053] (2) The uniformly mixed powder is placed in an alumina crucible and transferred to a muffle furnace for high-temperature sintering. The sintering procedure is to heat at 900°C for 8 hours and cool naturally to room temperature to obtain a positive electrode material.
[0054] (3) Collect the bulk material in the alumina crucible, grind it into powder, and store it in an argon glove box for future use.
[0055] The battery assembly process is the same as above, and can exhibit an initial discharge specific capacity of 80 mAh / g at a current density of 5 C, and an efficiency of 80% after 100 cycles.
[0056] Example 5
[0057] A cobalt-free sodium ion battery positive electrode material according to embodiment 5 of the present invention is prepared by the following steps:
[0058] (1) Lithium / Mg co-substituted Na 0.67 Ni x Li y Mg z Mn 0.67 O2 positive electrode material, wherein x=0.21, y=0.06, z=0.06; with a total mass of about 2 g, sodium carbonate, nickel acetate, lithium acetate, magnesium acetate, and manganese carbonate are mixed according to the stoichiometric amount shown, and after mixing evenly, the powder is placed in a drying oven at 80°C for drying;
[0059] (2) The uniformly mixed powder is placed in an alumina crucible and transferred to a muffle furnace for high-temperature sintering. The sintering procedure is to heat at 800°C for 12 hours and cool naturally to room temperature to obtain a positive electrode material.
[0060] (3) Collect the bulk material in the alumina crucible, grind it into powder, and store it in an argon glove box for future use.
[0061] The battery assembly process is the same as above, and can exhibit an initial discharge specific capacity of 85 mAh / g at a current density of 5 C, and an efficiency of 85% after 500 cycles.
[0062] Example 6
[0063] A cobalt-free sodium ion battery positive electrode material according to Example 6 of the present invention is prepared by the following steps:
[0064] (1) Lithium / Mg co-substituted Na 0.67 Ni x Li y Mg z Mn 0.67O2 positive electrode material, wherein x=0.19, y=0.08, z=0.06; with a total mass of about 2 g, sodium carbonate, nickel acetate, lithium acetate, magnesium acetate, and manganese carbonate are mixed according to the stoichiometric amount shown, and after mixing evenly, the powder is placed in a drying oven at 80°C for drying;
[0065] (2) The uniformly mixed powder is placed in an alumina crucible and transferred to a muffle furnace for high-temperature sintering. The sintering procedure is to heat at 900°C for 12 hours and cool naturally to room temperature to obtain a positive electrode material.
[0066] (3) Collect the bulk material in the alumina crucible, grind it into powder and store it in an argon glove box for later use. Figure 3 As shown in the figure, it shows the characteristics of plate-like particles with a size of micrometers. Its XRD pattern is as follows Figure 4 As shown, it can be seen that its diffraction peak is very consistent with the standard substance, indicating the existence of a P2 phase structure, and no impurity phase is observed, indicating that the positive electrode material is a pure phase.
[0067] Its rate performance is as follows Figure 5 As shown, the test voltage range is 2.5-4.3 V, and the current densities at 0.2C, 0.5C, 1C, 2C, 5C and 10C show 106.1, 102.3, 100.0, 97.2, 92.0 and 85.0 mAh g, respectively. -1 The discharge capacity.
[0068] Its cycling performance at 1C current density is as follows Figure 6 As shown, the test voltage range is 2.5-4.3V, and it can be seen that it exhibits about 99.5mAh g -1 After 150 cycles, the capacity retention rate is 91.4%.
[0069] Its cycling performance at 5C current density is as follows Figure 7 As shown, the test voltage range is 2.5-4.3V, and it can be seen that it exhibits about 90.3mAh g -1 After 600 cycles, the capacity retention rate is 80.3%.
[0070] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A cobalt-free sodium ion battery positive electrode material, characterized in that: The positive electrode material is a P2-type layered oxide material, and its general chemical formula is Na 0.67 Ni x M1 y M2 z Mn 0.67 O2, wherein M1 and M2 are any two of Mg, Cu, Li, Zn or Fe, x>0, y>0, z>0, and x+y+z=0.33, and magnesium ions, copper ions, lithium ions, zinc ions and iron ions replace part of the nickel ions.
2. A method for preparing a positive electrode material as claimed in claim 1, characterized in that: The following steps are involved: (1) according to the stoichiometric ratio of the chemical formula, a sodium salt in an amount of 1 to 1.05 times the stoichiometric amount of the required sodium element is mixed with the remaining metal salts in the required amount; (2) After drying, sintering at 500-900° C. for 4-20 h, and cooling to room temperature to obtain the positive electrode material.
3. The method for preparing the positive electrode material according to claim 1, characterized in that: The sodium salt described in step (1) is carbonate, acetate or oxalate, and the remaining metal salts described are one or more of carbonate, acetate or oxalate.
4. The method for preparing the positive electrode material according to claim 1, characterized in that: Before preparing the positive electrode material, the feasibility thereof is verified: 0.67 Ni 0.33 Mn 0.67 Take sodium salt, nickel salt and manganese salt and mix them evenly. Collect the powder after mixing and dry it. Transfer it to a muffle furnace and sinter it at 500-900℃ for 4-20h to obtain Na 0.67 Ni 0.33 Mn 0.67 O2 material.
5. The method for preparing the positive electrode material according to claim 1, characterized in that: The method also includes grinding the cooled positive electrode material into powder in a mortar, transferring the powder into a centrifuge tube, sealing the tube, and storing the tube in an argon glove box for later use.
6. A positive electrode plate for a sodium ion battery, characterized in that: The positive electrode sheet comprises the positive electrode material as claimed in claim 1.
7. A sodium ion secondary battery comprising the positive electrode sheet as claimed in claim 6.
Citation Information
Patent Citations
Magnesium-calcium modified layered P2-phase nickel-manganese-based positive electrode material as well as preparation method and application thereof
CN113809302A
Double-strategy modified layered oxide sodium-ion battery positive electrode material as well as preparation method and application thereof
CN114520323A
Method for preparing Cu and Zn-doped layered oxide sodium-ion battery positive electrode material with assistance of precursor and application of Cu and Zn-doped layered oxide sodium-ion battery positive electrode material
CN114715953A
P2 type layered metal oxide sodium ion battery positive electrode material and preparation method thereof
CN115394988A
Sodium-ion battery positive electrode material and preparation method thereof
CN117594785A